(untitled) - SALTIK, Sema; KIZILTAN, Güneş; BOZLUOLCAY, Melda (Cerrahpaşa Medical Journal, 2014)
Background.- Superficial siderosis of the nervous system is a rare condition caused by repeated subarachnoid hemorrhage. Observation.- We report a 58 year-old-man who had undergone surgery of cervical neurinoma 22 years ago. He was presented with progressive gait ataxia, hearing loss, dementia, anosmia and pyramidal signs. Disease - onset was 3 years ago. The diagnosis of superficial siderosis was made by means of Magnetic Resonance Imaging of the head, and was confirmed by increased iron level in the CSF. Since surgical treatment prevent further bleeding and possibly progression of the disease, the possible cause of bleeding and treatment options are discussed in this report.